Determinants Of Tourist Behaviour Towards The Marine Environment In Perhentian Island, Terengganu, Malaysia - Ramdas, Murugadas (2018)
An increase in development and tourism activities in small islands have caused degradation to the islands’ marine environment. Tourists’ behaviour has been identified as a factor that influences conservation of marine environment in small islands. This study investigates the direct and indirect effects of determinants related to tourist behaviour towards the marine environment. Socio-psychological factors such as environmental knowledge, Environmental Attitude, Personal Norm, and Subjective Norm were identified as determinants of tourist behaviour. The gap in knowledge that has been identified is the combination all these determinants in study in one study related tourist behaviour.